Gojaznost: važan prediktor metaboličkog sindroma - Bairwa, Sunil Kumar; Kumari, Savita; Khandelwal, Neelam; Dhaked, Gireesh Kumar; Dhaked, Sunita; Bhatt, Ravi (Scripta Medica, 2023)
Background/Aim: The leading avoidable cause of mortality in the world is obesity. It modifies how the body reacts to insulin, which might result in insulin resistance and an elevated risk of type 2 diabetes. Recent investigations have revealed a link between obesity and the metabolic syndrome. Therefore, it was intended for the current study to look at the prevalence of obesity and how it relates to the metabolic syndrome. Methods: 120 healthy males between 30-50 years of age were chosen from the general population of Kota district, Rajasthan, India and screened for obesity and divided in three groups: normal, overweight and obese. Each group comprised of forty subject. Serum was separated and run in department of biochemistry, GMC Kota. Anthropometric parameters were taken. The completely automated analyser ERBA EM 360 performed lipid profile and blood sugar analyses on serum. Result: Obesity increased metabolic syndrome prevalence. In comparison to overweight and normal weight people, obese subjects exhibited considerably lower levels of high-density lipoprotein (HDL) cholesterol and significantly higher levels of blood glucose, triglycerides, total cholesterol and low-density lipoprotein (LDL) cholesterol. Additional coronary artery disease (CAD) risk prediction ratios, such as total cholesterol/HDL, LDL/HDL and triglycerides/HDL ratios that have gradually increased from the normal to obese group, show that obese subjects have a relatively higher risk of developing cardiovascular diseases (CVD) than do those in the overweight and normal groups. Conclusion: One of the key elements of metabolic syndrome, which is a collection of clinical and metabolic anomalies including abdominal obesity, insulin resistance, hypertension and dyslipidaemia, is obesity. Each of these conditions raises the risk of CVD and diabetes mellitus type 2 directly. The progression towards diabetes and CVD can be prevented by lifestyle modification programmes and regular health checks (to explore the risk factors of metabolic syndrome).